Relating the Knowledge Production Function to Total Factor Productivity : An Endogenous Growth Puzzle - Joutz, Frederick (IMF Working Papers; Working Paper ;, 2005)
The knowledge production function is central to R and D-based growth models. This paper empirically investigates the knowledge production function and intertemporal spillover effects using cointegration techniques. Time-series evidence suggests there are two long-run cointegrating relationships. The first captures a long-run knowledge production function; the second captures a long-run positive relationship between TFP and the knowledge stock. The results indicate the presence of strong intertemporal knowledge spillovers and that the long-run impact of the knowledge stock on TFP is small. This evidence is interpreted in light of existing theoretical and empirical evidence on endogenous growth.